A continuous model for the joining of two fullerenes - D. Baowan (2018)
The successful design of many novel nano-electronic devices will require a thorough understanding of the geometric joining issues of certain nano-structures. In this paper, we adopt a continuous approach and we employ the calculus of variations to model the nanostructure obtained by the joining of two fullerenes. We model the fullerenes as spheres and we assume symmetric defects on both fullerenes so that the three-dimensional problem is axially symmetric and can therefore be reduced to a problem in two dimensions. We propose two models depending upon the curvature of the join profile which can be either positive or both positive and negative. However, there is at present no experimental or simulation data to verify the theoretical connecting structures predicted by this study.